2005
DOI: 10.1021/jp054334s
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Amines:  A Comparison of Electron-Donor Strengths

Abstract: The electron-donor abilities of ten aminophenyl systems and an additional aminothienyl system are compared using density functional theory calculations. The systems studied here include those with amine nitrogen atoms bearing alkyl or aryl groups and those with amine nitrogen atoms as part of a heterocycle. Their abilities to act as donors in electron-transfer processes are assessed from calculated vertical ionization potentials for the aminobenzenes, which are in good agreement with available experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 92 publications
(52 reference statements)
7
116
0
Order By: Relevance
“…Different from triphenylamine moieties, carbazole units show a more rigid molecular structure and poorer p-electron-donating ability than triphenylamie moieties, 66,67 which makes molecules containing carbazole units usually showing higher T g than their corresponding analogues bearing triphenylamine moieties. Similar to triphenylamine moieties, carbazole-based groups also have sp 3 hybridized nitrogen atoms, indicating their HI/HT capacity.…”
Section: Host Materials Bearing a Nitrogen-containing Aromatic Systemmentioning
confidence: 99%
“…Different from triphenylamine moieties, carbazole units show a more rigid molecular structure and poorer p-electron-donating ability than triphenylamie moieties, 66,67 which makes molecules containing carbazole units usually showing higher T g than their corresponding analogues bearing triphenylamine moieties. Similar to triphenylamine moieties, carbazole-based groups also have sp 3 hybridized nitrogen atoms, indicating their HI/HT capacity.…”
Section: Host Materials Bearing a Nitrogen-containing Aromatic Systemmentioning
confidence: 99%
“…37 Here, the tTPA pendant polymers (PTtTPA and PBTtTPA) exhibited higher HOMO levels than tCz pendant polymers (PTtCz and PBTtCz), presumably because of the lower oxidation potential and weaker electrondonating ability of carbazole derivatives. 38 Further, PBTtTPA and PBTtCz are expected to have higher HOMO levels than PTtTPA and PTtCz because of the longer conjugation length and p-electron delocalization in BT-based polymers compared to T-based polymers. Because no reversible n-doping process was observed in the CV spectra, the LUMO levels were estimated from the HOMO levels and UV-vis absorption E g using the equation:…”
Section: Electrochemical Properties Of Ptsmentioning
confidence: 99%
“…[11][12][13][14] Among all the materials studied, the NLO chromophores bearing 4-(dialkylamino)phenyl groups or triarylamine groups as a donating group were the most case due to their strong electrondonating ability and ease of synthesis. 18,19 However, there are few reports about additional amino groups, which are introduced into chromophore's donor part, how to infect chromophore's NLO activity and thermal stability. 16,17 Some studies have shown that by introducing additional electron-rich heteroatom group into the donor moiety could effectively enhance nonlinear optical property.…”
Section: Introductionmentioning
confidence: 99%